2023
DOI: 10.3390/cimb45100521
|View full text |Cite
|
Sign up to set email alerts
|

A Synopsis of Hepatitis C Virus Treatments and Future Perspectives

Christian Medina,
Alexis Hipólito García,
Francis Isamarg Crespo
et al.

Abstract: Hepatitis C virus (HCV) infection is a worldwide public health problem. Chronic infection with HCV can lead to liver cirrhosis or cancer. Although some immune-competent individuals can clear the virus, others develop chronic HCV disease due to viral mutations or an impaired immune response. IFNs type I and III and the signal transduction induced by them are essential for a proper antiviral effect. Research on the viral cycle and immune escape mechanisms has formed the basis of therapeutic strategies to achieve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 177 publications
0
1
0
Order By: Relevance
“…Interferons type I and HBV reactivation: Interferons type I (IFN-1) plays a crucial role in orchestrating the immune response during the reactivation of HBV. When viral components are recognized by PRRs such as Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I)-like receptors, and melanoma differentiation-associated protein 5, in liver cells known as hepatocytes and hepatic DCs, it leads to a reduced response to PAMPs and a compromised production of IFN-I, which include IFN-alpha and IFN-beta[ 27 , 28 ]. According to a report by Faure-Dupuy and Baumert[ 29 ], it has been found that HBV infection leads to an increase in the expression of microRNA-146a (miR-146a) in liver cells.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…Interferons type I and HBV reactivation: Interferons type I (IFN-1) plays a crucial role in orchestrating the immune response during the reactivation of HBV. When viral components are recognized by PRRs such as Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I)-like receptors, and melanoma differentiation-associated protein 5, in liver cells known as hepatocytes and hepatic DCs, it leads to a reduced response to PAMPs and a compromised production of IFN-I, which include IFN-alpha and IFN-beta[ 27 , 28 ]. According to a report by Faure-Dupuy and Baumert[ 29 ], it has been found that HBV infection leads to an increase in the expression of microRNA-146a (miR-146a) in liver cells.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…Innovative therapeutic strategies are being explored as well, to expand the treatment options for HCV especially for challenging cases (e.g., patients with HCC) as reviewed comprehensively by Medina et al [ 343 ]. For example, agents such as ezetimibe that target cellular cholesterol, which is critical for viral entry, can offer a novel mechanism to prevent HCV entry into hepatocytes [ 344 ].…”
Section: Treatment Of Hcvmentioning
confidence: 99%
“…Moreover, clinical trials incorporating statins with DAAs or IFN are underway [ 345 ]. These trials aim to enhance the antiviral response by taking advantage of the effects of statins on lipid metabolism, which may also boost IFN effectiveness [ 343 ].…”
Section: Treatment Of Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid potential confounding effects from known genetic backgrounds, we included interferon lambda 4 (IFNL4) in our considerations, which has been confirmed to be closely associated with HCV infection and the response to treatment. 28 Specifically, IFNL4 rs12979860 and IFNL4 rs8099917 are significantly associated with spontaneous virus clearance and response to peg-IFN-a/RBV treatment. 29 Therefore, these two SNPs were also included in the study, and their genetic typing results were incorporated as confounding factors in the final analysis to avoid the possible effect of the proven IFNL4 genotype on the HCV infection outcome.…”
Section: Introductionmentioning
confidence: 98%